Particle Physics in the LHC era - Barr, Giles (Oxford Master Series In Physics, 2016)
This book gives a modern introduction to particle physics. The main mathematical tools required for the rest of the book are developed in Chapter 2. A quantitative introduction to accelerator physics is presented in Chapter 3. Chapter 4 covers detector physics, with an emphasis on fundamental physical principles. Chapter 5 covers the static quark model, with applications to light mesons and baryons as well as heavier states containing charm and beauty quarks. Chapter 6 introduces relativistic quantum mechanics and uses spinors to relate Lorentz invariance to the Dirac equation. Chapter 7 covers the basics of the electroweak theory based on broken SU(2) × U(1) symmetry. Chapter 8 reviews some of the key experiments that led to the development of the electroweak theory. Chapter 9 explains the importance of deep inelastic scattering data for providing direct evidence for the existence of quarks. It also gives a brief introduction to quantum chromodynamics (QCD). Chapter 10 considers flavour oscillations in the quark sector and then discusses the evidence for CP violation. Chapter 11 examines the theory of neutrino oscillations as well as the evidence for these oscillations. Chapter 12 gives an elementary introduction to the Higgs mechanism as well as a careful explanation of the experimental evidence for the existence of a Higgs boson. Chapter 13 looks at LHC physics and explains how searches for Beyond the Standard Model Physics are performed. It concludes with a discussion of the evidence for dark matter and dark energy.